Pengaruh Jenis Bahan terhadap Proses Gasifikasi Sampah Organik Menggunakan Updraft Fixed Bed Reactor - Wira Widyawidura; Maria Ratih Puspita Liestiono; Muhammad Sigit Cahyono; Agus Prasetya; Mochammad Syamsiro (Proklamasi 45 University, 2017)
Organic wastes has potential as a renewable energy resource. The waste could be converted as a gaseous fuel through gasification method. The objective of this reserach was to study the performance of gasification of various organic waste using fixed bed updraft gasifier especially in term of production of heat and stability of gas production. The raw material that used are rice husk, sawdust pellet, and wood branch. The stabilization of gas production was measurdd based on the time interval of gas could be burnt. The result shows that the kind of biomass has influenced the heating rate and stability of gas production. Sawdust pellet have the biggest burning stabilisation, that is 45 minute of burning time, compare to rice husk that have 15 minute burning time, and wood branch that have 30 minutes burning time. The main problem of gasification of organic waste was less stabilization of gas production due to low material compaction and uncontinuous mass flow.